2004
DOI: 10.1111/j.1464-410x.2004.04815.x
|View full text |Cite
|
Sign up to set email alerts
|

Urodynamic findings before and after noninvasive management of bladder calculi

Abstract: OBJECTIVES To determine the most frequent urodynamic observations associated with bladder calculi, and to assess whether the presence of calculi alters these observations. PATIENTS AND METHODS Fifty patients with bladder stones were included in a prospective study in which two urodynamic tests were used, one at inclusion and another once the patient was stone‐ free after treatment by noninvasive methods (mainly extracorporeal shockwave lithotripsy). RESULTS The results from the urodynamic evaluation with the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 19 publications
1
14
1
Order By: Relevance
“…However, the need for routine surgery to relieve BOO in such patients has recently been questioned. 5 Our results confirmed that patients who receive conservative management of BPH after stone removal experience PSA, prostatic-specific antigen; SD, standard deviation. * Alpha-blockers included tamsulosin, naftopidil, and silodosin.…”
Section: Commentsupporting
confidence: 88%
See 1 more Smart Citation
“…However, the need for routine surgery to relieve BOO in such patients has recently been questioned. 5 Our results confirmed that patients who receive conservative management of BPH after stone removal experience PSA, prostatic-specific antigen; SD, standard deviation. * Alpha-blockers included tamsulosin, naftopidil, and silodosin.…”
Section: Commentsupporting
confidence: 88%
“…3,4 However, another prospective study found that only 51% of patients presenting with bladder stones had urodynamic evidence of BOO. 5 The total number of BPH surgeries has gradually declined since its peak in 2005. 6 This decline may have resulted from the development of effective medical treatments, including alpha-blockers, 5-alpha-reductase inhibitors, and combination therapy.…”
Section: Resultsmentioning
confidence: 99%
“…A urodynamics study can be helpful in evaluation and management of concomitant bladder dysfunction post stone removal 8. Most frequent urodynamic findings in patients with vesical calculi include presence of BOO in 51%, detrusor overactivity in 68% and detrusor underactivity in 10% of patients 9. In the present case, giant vesicle calculi formation may have occurred due to age-related voiding dysfunction and untreated chronic urinary tract infection.…”
Section: Discussionmentioning
confidence: 67%
“…The other trial in 50 consecutive men with bladder stones due to various underlying diseases, including BPE, showed in P/F studies BPO in 51%, detrusor underactivity in 10%, and detrusor overactivity in 68% of patients 34. Both trials indicate a possible association between bladder stone formation and BOO/BPO; however, detrusor underactivity or overactivity,34 or other types of BOO, such as urethral stricture, neurogenic bladder dysfunction, or prostate cancer,31 may also play a role. Data suggest that calculi remain lying in the bladder due to incomplete bladder emptying; therefore, any patient with PVR is at risk of developing bladder stones.…”
Section: Resultsmentioning
confidence: 97%
“…One trial in 100 patients with bladder stones not necessarily associated with LUTS/BPO or BPE reported about “obstruction” in 88%, a diagnosis based on symptoms and clinical judgment rather than P/F measurements 31. The other trial in 50 consecutive men with bladder stones due to various underlying diseases, including BPE, showed in P/F studies BPO in 51%, detrusor underactivity in 10%, and detrusor overactivity in 68% of patients 34. Both trials indicate a possible association between bladder stone formation and BOO/BPO; however, detrusor underactivity or overactivity,34 or other types of BOO, such as urethral stricture, neurogenic bladder dysfunction, or prostate cancer,31 may also play a role.…”
Section: Resultsmentioning
confidence: 99%